Doctoral Supervision in Russian Universities: to the Problem of Balancing Activity and Performance - B. I. Bednyi; N. V. Rybakov (Высшее образование в России)
Doctoral supervision is considered one of the key factors in doctoral education performance. High-quality supervision does not merely predict the success of dissertation completion, but also plays a major role in academic community integration and identity development of doctoral students. Publications exploring problems of supervision tend to be based on surveys into mentors’ functions and advisory styles. Currently, research that aims at evaluating supervision efficiency is scarce. In the present article, we derive quantification of advisors’ activity and performance from non-reactive data on academic staff appointed to supervise doctoral students at two research-intensive multidisciplinary universities. The empirical base for the study comprises the data on research supervisors (N=515) and their doctoral students (N=1597). The paper addresses two main questions: (1) how does the number of doctoral students assigned influence a supervisor’s performance; (2) is there a correlation between a level of performance of guided students and their supervisor’s position, academic degree, academic rank and citation metrics and publication productivity. The findings imply that there is a great disparity in distribution of supervisors by number of students and by performance level (number of dissertation defenses), which is found to conform to Pareto – Zipf law. The highest performers prove to be those staff members who supervise from two to five students. That share of staff members scores higher on citation metrics and demonstrates better publication activity. A large portion of this group consists of staff holding academic positions and lecturers who do not attain a Doctor of sciences degree or academic rank. Performance indicators proposed in the article along methods of data collection, processing and analysis could have practical implications for monitoring supervisors’ activity in universities. The results obtained form basis for a number of managerial propositions to enhance supervision performance level.